Competitive game technology at the stage of sports specialization of freestyle wrestlers in the Sakha Republic - Ponomarev V. V.; Efimov A. A.; Bartnovskaya L. A.; Kravchenko V. M. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to theoretically substantiate and develop the content of competitive gaming technology at the stage of sports specialization of freestyle wrestlers of the Republic of Sakha and test its effectiveness in experimental work.